Direct and Indirect Impacts of Oil Price Shocks on Ecuador’s Economic Cycles (2000:01-2020:01) - Martin-Mayoral, Fernando; Carvajal, Alexander (Estudios de Economía, 2023)
We analyse the non-linear relationship between oil price shocks and the real business cycle in Ecuador, a dollarized economy where oil exports are the country’s main source of foreign exchange. We estimate several autoregressive Markov switching models for the period 2000:01-2020:01 to identify the differentiated impact of nominal oil price shocks on real GDP in expansion and slowdown regimes. We find evidence that oil price shocks have an asymmetric effect on Ecuador’s economic growth, with a larger impact during slowdowns. They also affect all components of aggregate demand differently in each regime, with a larger impact on investment during expansions.